WASP and SCAR have distinct roles in activating the Arp2/3 complex during myoblast fusion. - Berger, S.; Schaefer, G.; Kesper, D.A.; Holz, A.; Eriksson, T.; Palmer, R.H.; Beck, L.; Klämbt, C.; Renkawitz-Pohl, R.; Önel, S.F. (Journal of Cell Science, 2008)
Myoblast fusion takes place in two steps in mammals and in Drosophila. First, founder cells (FCs) and fusion-competent myoblasts (FCMs) fuse to form a trinucleated precursor, which then recruits further FCMs. This process depends on the formation of the fusion-restricted myogenic-adhesive structure (FuRMAS), which contains filamentous actin (F-actin) plugs at the sites of cell contact. Fusion relies on the HEM2 (NAP1) homolog Kette, as well as Blow and WASP, a member of the Wiskott-Aldrich-syndrome protein family. Here, we show the identification and characterization of schwächling--a new Arp3-null allele. Ultrastructural analyses demonstrate that Arp3 schwächling mutants can form a fusion pore, but fail to integrate the fusing FCM. Double-mutant experiments revealed that fusion is blocked completely in Arp3 and wasp double mutants, suggesting the involvement of a further F-actin regulator. Indeed, double-mutant analyses with scar/WAVE and with the WASP-interacting partner vrp1 (sltr, wip)/WIP show that the F-actin regulator scar also controls F-actin formation during myoblast fusion. Furthermore, the synergistic phenotype observed in Arp3 wasp and in scar vrp1 double mutants suggests that WASP and SCAR have distinct roles in controlling F-actin formation. From these findings we derived a new model for actin regulation during myoblast fusion.